PENGARUH PROMOSI MELALUI MEDIA SOSIAL DAN KESADARAN MEREK TERHADAP MINAT BELI AIR MINUM DALAM KEMASAN DENGAN MEREK AQUA PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNS - Claudia Muslimawati; Sunarto Sunarto; Dewi Kusuma Wardani (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
This study aims to determine: (1) the influence of promotion through social media towards interest in buying drinking water in packaging with aqua brand to economic education students of Teacher Training and Education Faculty of Sebelas Maret University, Surakarta. (2) The influence of brand towards interest in buying drinking water in packaging with aqua brand to economic education students of Teacher Training and Education Faculty of Sebelas Maret University, Surakarta. (3) The influence of promotion through social media and brand awareness towards interest in buying drinking water in packaging with aqua brand to economic education students of Teacher Training and Education Faculty of Sebelas Maret University, Surakarta. Methods used in research is descriptive quantitative .The population of the research are students of economic education class year 2014 , 2015 , and 2016. The data collection technique used in this research is proportionate stratified random sampling, as many as 131 students. Data collection techniques used is the method survey by the analysis of multiple regression. Based on the results of the study, it can be concluded that: (1) There is a significant positive influence between promotion through social media towards interest in buying drinking water in packaging with aqua brand to economic education students of Teacher Training and Education Faculty of Sebelas Maret University, Surakarta. (Price t count> ttable or 2.081> 1.979 at 5% significance level). (2) There is a significant positive influence between brand awareness towards interest in buying drinking water in packaging with aqua brand to economic education students of Teacher Training and Education Faculty of Sebelas Maret University, Surakarta. (Price t count> ttable or 4,832> 1,979 at significance level 5%).